Conventionality Standards for Children in Conflict Zones: Colombian Case study - Luiz Guilherme Arcaro Conci; Konstantin Gerber (Opinión Jurídica)
The main objective of this paper is to identify the multilevel perspective of hu-man rights protection for children in armed conflicts. For that, the pro persona or pro homine principle may be applied. It consists of an interpretative instru-ment provided by art. 29 of the American Convention of Human Rights and by art. 41 of the Convention on the Rights of the Child. The present analysis tackles distinct levels of protection, both at an international level and at the national level in Colombia and uses the pro homine principle to resolve eventual conflicts between the International Human Rights Law and domestic law.